SPATIAL SYNTAX: STUDY BETWEEN SPATIAL CONFIGURATION AND SOCIAL INTERACTION IN THE FACULTY OF ARCHITECTURE IN CONSTANTINE - Benkechkache, Imane; Kaghouche, Mehdi (International Journal of Innovative Technologies in Social Science, 2023)
This article deals with the impact of the architectural spatial configuration on the social behavior of its occupants, through the analysis of some syntactic measures. In this regard, several definitions have been considered on this topic where they have defined the spatial configuration as the simultaneous relations that exist between the parts and that constitute the totality (Hillier & Vaughan, 2007). Any physical environment has a close relationship with the social one, without forgetting that space is a fundamental need of the human being and it has to respond to its needs in order to reach an optimal degree of spatial satisfaction. Among the educational spaces, the faculty buildings within the university, present a social environment that allows students to socialize, share interests, develop relationships within groups, and feelings of belonging. Social behaviors, social interactions, and student gathering areas in faculty buildings are important issues from the perspective of architectural programming and architectural design performance. For this reason we took for this study the method of the spatial syntax that will help us to study this issue, A variety of theories have successfully indicated this method that will facilitate us to study the relationship between spatial configuration and pedestrian movement in various urban structures (Hillier et al., 1993; Hillier,Yang, & Turner, 2012; Sharmin & Kamruzzaman, 2018). We took for this study the faculty of architecture at the University of Constantine in Algeria. Using the tool "DEPTHMAP» software will allow us to draw the configurational characteristics of the corpus of our study area. The confrontation of the results of the analysis of the spatial syntax showed a correlation between the spatial properties and the social movement within the faculty, it has a direct impact of the spatial configuration on the behavior of the students inside the faculty in the use of the spaces of circulations, exchanges and gathering, as well as, on the visibility and the movement the accessibility in the use of the spaces by its occupants